Genetics of prelingual isolated deafness and Usher syndrome in the Maghreb and Jordan: Harnessing the potential of homozygosity - Zied Riahi; Sophie Boucher; Samia Abdi; Fabienne Wong Jun Tai; Amrit Singh-Estivalet; Asadollah Aghaie; Magali Niasme-Grare; Jean-Pierre Hardelin; Asma Behlouli; Malika Dahmani; Sonia Talbi; Yosra Bouyacoub; et al. (Proceedings of the National Academy of Sciences, 2025)
The molecular genetic diagnosis of prelingual sensorineural hearing impairment (HI) is essential for genetic counseling and patient management. Effective diagnosis requires a knowledge of the genetic architecture of HI, which is often lacking. We established a cohort of 450 unrelated patients with familial (at least two affected relatives) severe-to-profound bilateral prelingual HI in five countries with high consanguinity rates: Tunisia, Jordan, Algeria, Morocco, and Mauritania (the TJAMM cohort). Recessive and dominant inheritance were observed in 92% and 8% of cases, respectively; 14% were syndromic. Genome analysis detected 211 different mutations (36% not reported before) in 49 deafness genes, and fully resolved 90% of cases of autosomal recessive isolated deafness (DFNB forms), 89% of the mutations being homozygous. The deafness genes involved were similar in different countries, but their mutations, except a few in GJB2 and LRTOMT , differed considerably, suggesting an overrepresentation of private mutations. Biallelic missense mutations in MYO7A , CDH23 , PCDH15 , USH1C cause either DFNB forms or Usher syndrome type 1 (USH1) ( USH1/DFNB genes). Such mutations were overrepresented (13% of patients), highlighting the importance of distinguishing between these two mutation classes. We hypothesized that current difficulties might stem from the misclassification of certain mutations. By studying the 65 USH1/DFNB missense mutations reported to cause DFNB in the homozygous state, we identified some that, when associated with a loss-of-function mutation, resulted in USH1, a characteristic pattern of some recessive hypomorphic mutations. This reappraised classification of USH1/DFNB mutations has the potential to improve molecular diagnosis and patient management significantly.